Asymmetric decarbonization in the digital age: divergent pathways of advanced versus emerging economies - Yue, Mingyang; Ren, Biao; Zhu, Tao; Jin, Zhida (Frontiers in Environmental Science, 2025)
Digital technologies are increasingly vital catalysts for industrial green transitions, yet their heterogeneous decarbonization impacts across development countries tiers remain underexplored. We pioneer a novel Hypothetical Extraction Method (HEM) to quantify digital empowerment, revealing asymmetric pathways using sectoral data from 43 economies: Advanced economies exhibit a U-shaped trajectory where digitalization initially reduces emissions/intensity but induces rebound effects beyond optimal thresholds, while emerging economies show an inverted U-curve for domestic digital inputs. Mechanistic analyses confirm technology and scale effects universally exist, but structural effects diverge—digitalization raises capital returns in advanced economies yet reinforces coal dependence in developing contexts. Foreign digital sources demonstrate positive environmental returns in emerging economies. Sectorally, digital technologies function as carbon catalysts in manufacturing through automation efficiencies but act as transitional carbon amplifiers in services due to platform-induced energy rebounds. These findings challenge linear decarbonization assumptions and provide empirical foundations for bifurcated digital-climate policies tailored to national development stages.